Ethnobiology and symbolic roles of plants and animals in Javanese funeral rituals, Central Java, Indonesia - LATIFAH RESTU PINASTI; MALFA AMORITA IFTITANI; MALIKASARI MALIKASARI; M. BAHRUL MUNA; SEVIANNA DANAH ZULFANI; MUHAMMAD INDRAWAN; TITI WAHYUNI; SURAPON SAENSOUK; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Pinasti LR, Iftitani MA, Malikasari, Muna MB, Zulfani SD, Indrawan M, Wahyuni T, Saensouk S, Setyawan AD. 2025. Ethnobiology and symbolic roles of plants and animals in Javanese funeral rituals, Central Java, Indonesia. Biodiversitas 26: 4805-4820. This study explores the ethnobotanical and ethnozoological dimensions of funeral and post-funeral traditions among the Javanese Muslim community in Kalibawang, Wonosobo District, Central Java, Indonesia. The research aimed to document the species of plants and animals used in ritual practices, their symbolic meanings, and their integration with Islamic and local cultural values. A descriptive–exploratory approach was employed, combining qualitative interviews with 90 respondents, field observations, and quantitative analysis using the Relative Frequency of Citation (RFC) index. The findings revealed 19 plant species and 4 animal species involved in various stages of the ritual process. Flowers and leaves were the most frequently used plant parts, particularly Jasminum polyanthum, Magnolia × alba, Cananga odorata, and Oryza sativa, which held the highest RFC values (0.67-0.87). Among animals, Gallus domesticus ranked highest (RFC 0.67), followed by Bos indicus and Oreochromis spp.. These species function as ritual mediators expressing purity, devotion, fertility, and gratitude. The integration of Islamic principles with Javanese cosmology forms a harmonious synthesis that sustains both spiritual and ecological values. Moreover, the continuous use and cultivation of ritual species in homegardens contribute to biodiversity conservation through cultural continuity. The study concludes that the Kalibawang funeral tradition represents a living model of biocultural sustainability, where religious belief, cultural identity, and environmental stewardship coexist in a dynamic equilibrium that strengthens community resilience and moral ecology.